Ultra-High Stokes Shift in Polycyclic Chromeno[2, 3-b]Indoles. (21st April 2022) - Rajbongshi, Basanta Kumar; Bhattacharyya, Himangshu Pratim; Pegu, Choitanya Dev; Sharma, Sagar; Baruah, Pranjal K.; Sarma, Manabendra
Abstract:  Three polycyclic chromeno[2, 3 -b ]indolecontaining indole and naphthalene rings fused by a pyran ring were synthesized by metal-free C–H functionalization method and their photophysical studies were done. Steady state absorption spectra do not show solvent effect while fluorescence spectra exhibit solvatochromic shift. The molecules exhibit ultra-high Stokes shift of the order of 3.07 eV (24, 696 cm −1 ) in acetonitrile and 2.12 eV (17, 054 cm −1 ) in ethyl acetate. To corroborate experimental observation, we performed computational investigation both in gas and solvent phases. The computed results are in good agreement with the experimental observation. Analysis of the frontier molecular orbitals as well as natural transition orbitals depicts intramolecular charge transfer in the molecules. Further, gas phase as well as solvent phases optimized structures in the ground and excited states of all chosen molecules show increase in planarity in the excited state. An excited state intramolecular charge transfer accompanied by structural relaxation leading to planarity in the excited state has been suggested to cause large Stokes shifted fluorescence emission in these molecules. Graphical Abstract: